LEGAL REVIEW OF PROTECTION ORDERS FOR VICTIMS OF DOMESTIC VIOLENCE - Berliana Putri Pramesti; Bambang Widarto; Diding Rahmat (JILPR Journal Indonesia Law and Policy Review, 2026)
Domestic violence is a form of human rights violation that causes physical, psychological, sexual, and economic suffering for victims. In order to provide protection for victims, the state enacted Law Number 23 of 2004 concerning the Elimination of Domestic Violence, which regulates the issuance of a Protection Order as one of its legal mechanisms. This legal instrument aims to provide preventive protection for victims from the risk of repeated violence and to ensure their safety during the law enforcement process. This study aims to analyze the regulation of protection orders for victims of domestic violence under Law Number 23 of 2004 and their implementation in law enforcement practices in Indonesia. This research employs a normative legal research method with a statutory approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials which are analyzed qualitatively through legal interpretation and juridical reasoning. The results of this study indicate that the regulation of protection orders in the Domestic Violence Law plays an important role as a preventive legal protection instrument for victims. Protection orders can be granted in the form of temporary protection provided by law enforcement officials as well as permanent protection determined by the court. However, in practice, the implementation of protection orders still faces several challenges, including the low level of public legal awareness, limited access of victims to protection services, and the lack of optimal coordination among law enforcement agencies. Therefore, it is necessary to enhance the capacity of law enforcement officials, strengthen coordination among relevant institutions, and increase legal awareness through public education so that the protection of domestic violence victims can be implemented effectively.